A CONTRIBUIÇÃO DO PIBID HISTÓRIA UFN NA FORMAÇÃO INICIAL E CONTINUADA DOS BOLSISTAS SUPERVISORES, BOLSISTAS ID EGRESSOS E BOLSISTAS ID EGRESSOS NA PÓS-GRADUAÇÃO STRICTO SENSU - Scherer, Jociléia (2018)
This research aims to analyze the general perceptions about the contributions the PIBID/History/UFN in initial and Continuing of the scholars and scholars of the supervisors teaching graduates, who worked in the period from 2014 to 2016, and its implications for the teaching of history.The specific objectives were: to verify the perceptions of the scholars on the methodologies that developed during the period that acted in the PIBID, through the questionnaire answered; identify academic and thematic productions of works presented at events during the period from 2014 to 2016 of the scholar’s supervisors, scholarship at graduation, and study in a historical perspective to PIBID. The methodology used was based on the interpretative paradigm, under a qualitative, exploratory case study type-description and analysis of documents of the Subproject PIBID history of Franciscan University-UFN.The subject of this research were twelve, the total, four scholar’s supervisors, three scholars of initiation to teaching graduates who served in the classroom and five fellows from initiation to teaching graduates that were inserted into the post-graduate Stricto-Sensu research instruments were questionnaires, partial reports of the Subproject PIBID/History/UFN 2014 to 2016 and of Curriculum Lattes of the investigated. Data analysis was based on Discursive Textual analysis.It can be concluded that, by means of this study, it was considered that the contribution of the PIBID/History/UFN was relevant to the construction of personal and professional trajectory of the scholars of initiation to teaching graduates and supervisors, to the extent that collaborated to the improvement of scientific research, through an intense participation of the scholars at events and the renewal of methodological approaches.